تاريخ الجزائر السياسي في الفترة 1962-1978 من خلال كتابات محمد العربي الزبيري - رضا مصباحي; مسعود قية (University of Eloued جامعة الوادي, 2025)
"عرفت الجزائر ظهور العديد من المؤرخين الذين دونت أقلامهم حقائق وأحداث للفترة الاستعمارية وما بعدها، ولعل أبرزهم المؤرخ محمد العربي الزبيري الذي كان له دورا بارزا في تدوين تاريخ الجزائر السياسي خلال العديد من الحقب الزمنية ومنها فترة (1962-1978م)، هذه الفترة الحاسمة من تاريخ الدولة الجزائرية والعصيبة بسبب العديد من الأحداث أهمها: الصراع على السلطة واختلاف في التوجهات السياسية والإيديولوجيات وجهات النظر حول العديد من القضايا الداخلية والإقليمية والدولية. ومن خلال هذا تمكننا كتابات الزبيري من إعطاء صورة واضحة لهذه الأحداث والتحولات السياسية والاقتصادية على الصعيدين الداخلي والخارجي، لأنها تأخذ أهميتها كون هذه الشخصية لم تكن فقط ناقلة بل كانت شاهدة وفاعلة في جزء كبير منها " " Algeria has witnessed the emergence of many historians who have documented the facts and events of the colonial period and its aftermath. One of the most prominent historians is Mohamed Larbi Zbiri who played an important role in documenting Algeria's political history over many periods including the period (1962-1978). In fact, this crucial period in the history of the Algerian state was turbulent due to many events including the struggle for power, the differences in political orientations, ideologies and viewpoints on many domestic, regional, and international issues. Zbiri's writings works on enabling us to provide a clear picture of these events and their political and economic transformations, both domestically and internationally. This is important because this figure was not only a transmitter, but also a witness and active participant in many of them. "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعصر
Keywords: التحولات السياسية و الاقتصادية; الفترة الإستعمارية; الإيديوليجيات; the colonial period; Ideologies; political and economic transformations